Simulating the effect of climate change on soil microbial community in an Abies georgei var. smithii forest - Fu, Fangwei; Li, Jiangrong; Li, Yueyao; Chen, Wensheng; Ding, Huihui; Xiao, Siying (Frontiers in Microbiology, 2023)
The Qinghai-Tibet Plateau is considered one of the regions vulnerable to the effects of climate change. Studying the effects of climate change on the structure and function of soil microbial communities will provide insight into the carbon cycle under climate change. However, to date, changes in the successional dynamics and stability of microbial communities under the combined effects of climate change (warming or cooling) are not known, which limits our ability to predict the consequences of future climate change.In this study, the insitu soil columns of a Abies georgei var. smithii forest at 4300m and 3500m elevation in the Sygera Mountains were incubated in pairs for 1 year using the PVC tube method to simulate climate warming and cooling, corresponding to a temperature change of ±4.7°C. Illumina HiSeq sequencing was applied to study the alterations in soil bacterial and fungal communities of different soil layers.The results showed that warming did not significantly affect the fungal and bacterial diversity of the 0-10 cm soil layer, but the fungal and bacterial diversity of the 20-30 cm soil layer increased significantly after warming. Warming changed the structure of fungal and bacterial communities in all soil layers (0-10 cm, 10-20 cm and 20-30 cm) and the effect was greater with increasing soil layers. Cooling had almost no significant effect on fungal and bacterial diversity in all soil layers. Cooling changed the structure of fungal communities in all soil layers, but had no significant effect on the structure of bacterial communities in all soil layers, because fungi are more adapted than bacteria to environments with higher soil water content and lower temperatures. Interestingly, a warmer climate could create more ecological niches for microbial species to coexist and increase the strength of microbial interactions, while a cooler climate could have the opposite effect. However, we found differences in the intensity of microbial interactions in response to climate change in different soil layers.